PENGARUH PENGALAMAN KERJA, LATAR BELAKANG PENDIDIKAN DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PADA PT. PEGADAIAN PERSERO CABANG RANTAUPRAPAT - Pitriyani, Pitriyani; Halim, Abd. (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2020)
This study aims to analyze whether work experience, educational background and compensation affect employee performance at PT. Pegadaian Persero Branch Rantauprapat. The hypothesis contained in this study is that work experience, educational background and compensation have a significant effect on employee performance either partially or simultaneously. The population of this research is the permanent employees of PT. Rantauprapat Branch Pegadaian. The method used in this research is descriptive and verification methods. The data used by researchers is data that is made in the form of a closed questionnaire, all of which use the SPSS 21 program. Based on the results of the study it can be seen that the effect of work experience , educational background and compensation for employee performance, either partially or simultaneously have a positive and significant effect.